Multiplicative Perturbations of Convoluted C-Cosine Functions and Convoluted C-Semigroups - Fang Li; Huiwen Wang; Jun Zhang (Journal of Function Spaces and Applications)
We obtain the multiplicative perturbation theorems for convoluted C-cosine functions (resp., convoluted C-semigroups) and n-times integrated C-cosine functions (resp., n-times integrated C-semigroups) for n∈ℕ. Moreover, we obtain some new results for perturbations on C-cosine functions (resp., C-semigroups). Some examples are presented.